Ryzyko w sektorze finansów publicznych ze szczególnym uwzględnieniem finansów samorządowych - kwestie wybrane - Korenik, Dorota (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
This article presents kinds of risk connected with functioning public sector and risk's deciding factors. Especially the problems apply to Polish local self-governmental sector. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 40-51